Cimicifuga racemosa extract for relieving menopausal symptoms: A randomized controlled trial - P. Tanmahasamut (2018)
© 2015 International Menopause Society. Objectives: To evaluate the effectiveness of black cohosh extract 40 mg/day for relieving moderate to severe menopausal symptoms and improving quality of life in Thai women. Methods: A randomized, double-blind, placebo-controlled clinical trial was conducted in a menopause clinic of a tertiary-care university hospital during 2011-2013. Participants were peri- or postmenopausal Thai women aged at least 40 years, who have moderate to severe menopausal symptoms evaluated using the Kupperman index (KI). Outcome measures included KI, frequency of hot flushes, Menopause-Specific Quality of Life (MENQOL) score, participants' global satisfaction and safety outcomes. Results: There were 54 participants assigned to treatment (black cohosh extract 40 mg/day, n = 27) or placebo group (n = 27). Both the treatment and placebo groups had comparable baseline KI scores (33.9 ± 7.9 vs. 31.3 ± 6.8), frequency of hot flushes (3.1 ± 2.0 vs. 2.8 ± 2.1), and MENQOL scores, all of which improved with time. Neither the improvements nor the global satisfaction were significantly different between the two groups; but the proportion of participants with moderate to severe symptoms seemed to be lower in the treatment group than in the placebo group (40% vs. 60%, p = 0.174). There was no serious adverse event or significant change in liver function tests. Conclusions: A black cohosh extract of 40 mg/day is not superior to a placebo for relieving moderate to severe menopausal symptoms or improving quality-of-life scores in Thai women.